Seed morphobiometry of wild and cultivated taxa of Phaseolus L. (Fabaceae) - Leonardis, W. de; Santis, C. de; Fichera, G.; Torrisi, A.; Padulosi, S. (2011)
A morphobiometric analysis of seeds of Phaseolus L. from 50 populations belonging to 31 wild and cultivated taxa was carried out. Based on the outcome of the study an identifi cation key was developed comprising 25 morphotypes of which 23 related to individual taxa The different patterns of seminal tegument allowed 31 taxa to cluster into three groups: (1) Phaseolus angustissimus Gray group (wrinkled seed coat) with two morphotypes, (2) Phaseolus lunatus L. group (smooth tegument with striae) with ten morphotypes and (3) Phaseolus vulgaris L. group (smooth tegument without striae) with 13 morphotypes. All the taxa exhibited uniformity in size and variability in tegument colour of seeds irrespective of the source of population and the type of habitat. Characterization of taxa into defi nite morphotypes and the groups could be useful for biosystematic investigations and the markerbased genetic selection approaches in this important leguminous crop.